PENGARUH PROMOSI, FASHION INVOLVEMENT, DAN SHOPPING LIFE STYLE, DAN IMPULSE BUYING DI E-COMMERCE SHOPEE - Muhammad Rizki Maulana Putra; M. Alimul Kabir Albant; Laeli Novita Sari; Vicky F Sanjaya (STIE Bakti Bangsa Pamekasan, 2020)
The purpose of this study was to determine the effect of Sales Promotion / Promotion, Fashion involvement, and Shopping lifestyle on Impulse Buying in an E-Commerce shopee. This research uses quantitative methods, in this study. data collection through questionnaires distributed to respondents via social media. The sample in this study were users and consumers of Shopee with a total of 64 respondents. The statistical test was carried out by using PLS-based Structural Equation Modeling. The validity test uses the factor loading value, while the reliability is tested using the Cronbach alpha value, composite reliability, and Average Variance Extracted (AVE). After the results of the overall indicator items used are valid, and also reliable, then a Hypothesis Test is carried out. From the three proposed hypotheses, all three can be accepted. Based on the research results, it is found that Sales Promotion has a positive effect on Impulse Buying, Fashion Involvement has a positive effect on Impulse Buying, and Shopping Life Style has a positive effect on Impulse Buying in E-Commerce Shopee